Islamic Education in Building Personal and Community - Nurbaeti, Nurbaeti; Suharyat, Yayat (International Journal of Global Sustainable Research, 2023)
Islamic education is a conscious effort to direct and develop one's talents in terms of physical and spiritual. This study aims to gain an understanding of how Islamic education builds personal and community. The method used in this study is literature review. The results of the discussion of this study show that the types of Islamic educational institutions are not only in Madrasas, but in homes, mosques, Taklim assemblies and Islamic boarding schools. This research can be concluded that Islamic education in building personal and community is needed. Because personal building such as character building, spiritual awareness, skills and knowledge, independence and empowerment are all taught in Islamic education. Then in building communities taught social solidarity, balance between individuals and communities, tolerance of diversity and just and responsible leadership requires Islamic education.